Effect of Mg incorporation on the properties of PCL/Mg composites for potential tissue engineering applications - Nuthana Kalva, Sumama; Ali, Fawad; Subhadra Keyan, Kripa; Khan, Omar M.; Pasha, Mujaheed; Velasquez, Carlos A.; Koç, Muammer (Frontiers in Materials, 2024)
Polycaprolactone (PCL) is a biocompatible polymer that is readily moldable into a variety ofvarious shapes and designs, including scaffolds. However, its inherent low mechanical strength and slow biodegradation restricts restrict its use in tissue engineering. Magnesium (Mg), a biocompatible metal with excellent osteoconductivity and biodegradability, is a promising choice for bone for tissue engineering applications. This study investigates the influence of Mg incorporation on the properties of PCL/Mg composites, aiming to evaluate their suitability for 3Dprintable (3DP) tissue engineering applications. We synthesized a series of PCL/Mg composites with varying Mg concentrations and characterized their mechanical, thermal, and degradation properties. This research article focuses on assessing the effect of Mg on the properties of PCL/Mg composites thereby paving the way for potential breakthroughs in tissue engineering applications.According to microscopicSEM analysis of the composite films, the Mg particles are dispersed consistently throughout all the compositions. The findings demonstrated that adding Mg influenced PCL's mechanical and thermal properties. The mechanical test results showed that the tensile strength of 15% Mg composite filaments improved by around 10% compared to the neat PCL filaments, but the. However, the elastic modulus decreased by around 50% for the same composition. The thermal study revealed that there was a significant reduction in the degradation temperature from above 400 0 C for pure PCL to around 300 0 C for PCL/Mg composite having 15% Mg. Additionally, the weight loss that occurred during in vitro degradation showed that the composite samples' degradation rate had been significantly increased by the presence of Mgthe presence of Mg had significantly increased the degradation rate of composite samples. Also, Mg incorporation influences cell adhesion as well, with better attachment observed for 10% Mg 3DPprinted samples. Overall, PCL/Mg composites offer a solution to overcome the limitation of low thermos-mechanical properties typically associated with the PCL.